2022
DOI: 10.1021/acsami.2c12484
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prussian White@MnO2-Based Inorganic Electrochromic Energy Storage Devices with Integrated Flexibility, Multicolor, and Long Life

Abstract: Flexible electrochromic devices have attracted considerable attention in recent years due to their great potential in smart multifunction electrochromic energy storage devices and wearable intelligent electronics. Herein, we present an inorganic flexible Li-based electrochromic energy storage device (EESD) by combining a Prussian white@MnO 2 -composited electrode (PWM) and sputtering-made WO 3 electrode. The synergistic effect of Prussian white and MnO 2 plays a positive role both in energy storage and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…With the cyclic process continuing, both the colored and bleached transmittance exhibited a rising trend, which means the partial electrode materials failed. Combined with the previous study, it is observed that it could be due to the poorer stability of MnO 2 compared with that of PB . For this inorganic flexible device, its mechanical flexibility combined with the electrochromic performance was also checked, as in Figure b–d.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…With the cyclic process continuing, both the colored and bleached transmittance exhibited a rising trend, which means the partial electrode materials failed. Combined with the previous study, it is observed that it could be due to the poorer stability of MnO 2 compared with that of PB . For this inorganic flexible device, its mechanical flexibility combined with the electrochromic performance was also checked, as in Figure b–d.…”
Section: Resultssupporting
confidence: 52%
“…Combined with the previous study, it is observed that it could be due to the poorer stability of MnO 2 compared with that of PB. 63 For this inorganic flexible device, its mechanical flexibility combined with the electrochromic performance was also checked, as in Figure 5b−d. The electrochemical process would be affected when the bending radius was lower than 3 cm (Figure 5b), but even under a small bending radius (1.5 cm), the capacity retention can still get up to ∼80%, which verified its good flexible function (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…The CE is also an essential parameter for electrochromic materials, it can be calculated using the following equation normalC normalE ( λ ) = normalΔ A Q normald = log nobreak0em.25em⁡ T normalO normalX T normalr normale normald Q normald …”
Section: Resultsmentioning
confidence: 99%
“…The CE is also an essential parameter for electrochromic materials, it can be calculated using the following equation …”
Section: Resultsmentioning
confidence: 99%
“…53 This problem can be effectively solved by the introduction of structural colors and the preparation of composite materials. 54,55 The great advantage of organic EC materials compared to inorganic materials is that the color can be tuned by means of molecular structural design. [56][57][58] Of course, structural colors and color composites are also common means of color modulation in organic materials.…”
Section: Ec Materials For Color Camouflagementioning
confidence: 99%